Metoprolol and sertraline combined treatment may increase the risk of bradycardia - Protopapas, Andreas; Lambrinou, Ekaterini (My University, 2020)
Patients with cardiovascular disease (CVD) commonly have anxiety and depressive disorders. They may need to take selective serotonin reuptake inhibitors (SSRIs) along with metoprolol, one of the most common drugs prescribed to patients with CVD. This is a case study of a 64-year-old woman who developed severe sinus bradycardia after taking metoprolol for the management of paroxysmal atrial fibrillation (AF) and sertraline treatment of depression symptoms. Despite the fact that sertraline is a weaker inhibitor of CYP2D6, it may increase the risk of severe bradycardia. Health professionals need to be aware of this possible interaction and conduct clinical monitoring of heart rate and electrocardiogram during combined treatment, and to encourage the patients to self-monitor for bradycardia.
Keywords: Fluvoxamine; Mirtazapine; Norsertraline